Improving social skills in children with personality traits shyness - Said, Astri Ardiyanti; Iswinarti, Iswinarti (Universitas Muhammadiyah Malang, 2024)
Shyness can manifest as inhibition, fear, and avoidance in the context of new social environments and perceived social evaluation situations. Individuals with shyness show symptoms from cognitive, emotional and behavioral aspects. The assessment method used is observation interviews and using psychological test tools. The intervention used is social skills training with the modeling technique which is carried out in eight sessions. Social skills are the ability to express oneself when interacting with others, being able to read and understand any social situation, having knowledge of social roles, norms, and rules. The modeling technique helps children imitate the behavior of the model to change the subject’s behavior in the social environment, so that the modeling technique can help subjects improve social skills. The results of the intervention show that the modeling technique can improve social skills in children with shyness personality traits.Rasa malu dapat bermanifestasi sebagai sikap inhibisi, ketakutan, dan penghindaran dalam konteks lingkungan sosial baru dan situasi evaluasi sosial yang dirasakan. Individu dengan rasa malu menunjukkan gejala dari aspek kognitif, emosional, dan perilaku. Metode penilaian yang digunakan adalah wawancara observasi dan menggunakan alat tes psikologi. Intervensi yang digunakan adalah pelatihan keterampilan sosial dengan teknik modeling yang dilakukan dalam delapan sesi. Keterampilan sosial adalah kemampuan untuk mengekspresikan diri ketika berinteraksi dengan orang lain, mampu membaca dan memahami situasi sosial apa pun, memiliki pengetahuan tentang peran, norma, dan aturan sosial. Teknik modeling membantu anak meniru perilaku model untuk mengubah perilaku subjek di lingkungan sosial, sehingga teknik modeling dapat membantu subjek meningkatkan keterampilan sosial. Hasil intervensi menunjukkan bahwa teknik modeling dapat meningkatkan keterampilan sosial pada anak dengan ciri kepribadian pemalu.